Capital Flight and the Economic Growth: Evidence from Nigeria - Adedoyin I. Lawal; Kelechi Promise Kazi; Johnson Olabode Adeoti; Osagie Godswill Osuma; Sunday O. Akinmulegun; Bamidele Ilo (Bina Nusantara University, 2017)
This research examined the impact of capital flight and its determinants on the Nigerian economy using the Autoregressive Distributed Lag (ARDL) model to analyze data source from the period of 1981 to 2015. The variables included current account balance, capital flight, foreign direct investments, foreign reserve, inflation rate, external debt, and the real gross domestic product. It was to examine the existence of a long run relationship among the variables studied. The result indicates that capital flight has a negative impact on the economic growth of Nigeria. Therefore, there is a need for government to implement policies that will promote domestic investment and discourage capital flight from Nigeria.